2022
DOI: 10.1038/s41398-022-02060-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of common risk variation in the recurrence risk of schizophrenia in multiplex schizophrenia families

Abstract: Multiplex families have higher recurrence risk of schizophrenia compared to the families of sporadic cases, but the source of this increased recurrence risk is unknown. We used schizophrenia genome-wide association study data (N = 156,509) to construct polygenic risk scores (PRS) in 1005 individuals from 257 multiplex schizophrenia families, 2114 ancestry-matched sporadic cases, and 2205 population controls, to evaluate whether increased PRS can explain the higher recurrence risk of schizophrenia in multiplex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…We have previously shown that members of the Irish Study of High-Density Schizophrenia Families (ISHDSF) 16 have an increased PRS for SCZ, bipolar disorder (BIP) and major depressive disorder (MDD) compared with population controls. 17 , 18 In this study, we sought to examine the differential relationship between PRSs for these three major psychiatric disorders, and quantitative measurement of symptom severity in the ISHDSF sample.…”
Section: Aimsmentioning
confidence: 99%
“…We have previously shown that members of the Irish Study of High-Density Schizophrenia Families (ISHDSF) 16 have an increased PRS for SCZ, bipolar disorder (BIP) and major depressive disorder (MDD) compared with population controls. 17 , 18 In this study, we sought to examine the differential relationship between PRSs for these three major psychiatric disorders, and quantitative measurement of symptom severity in the ISHDSF sample.…”
Section: Aimsmentioning
confidence: 99%